Comparison of two growth charts in Lesotho: health workers' ability to understand and use them for action - Ruel, Marie T.; Pelletier, David L.; Habicht, Jean-Pierre; Mason, John B.; Chobokoane, C. S.; Maruping, Arapang P. (American Public Health Association, 1991)
BACKGROUND: Two growth monitoring charts widely used for growth monitoring in Africa (the Road-to-Health (RTH) and the Growth Surveillance (GS] were compared in order to assist the Government of Lesotho to decide on an appropriate national growth chart. METHODS: Thirty-four health workers were taught and tested on the RTH during a first week of training and on the GS during a second week (the RTH-GS group), while the order was reversed for another 25 trainees (the GS-RTH group). The health workers were trained and tested on their ability not only to use and interpret the two charts, but also to make the right decisions about specific actions to be taken when growth faltering occurs. RESULTS: There was no difference between scores to the RTH and GS charts after one week of training. After the second week of training, the scores to the RTH chart improved and became better than those to the GS chart. The scores to the GS test did not increase with previous knowledge of the RTH chart. CONCLUSIONS: For this reason and others discussed in the paper, the RTH chart was recommended for nationwide use in Lesotho. The adoption of this recommendation was facilitated by the close involvement in this research of public and private agencies responsible for growth monitoring in Lesotho.